“If he returns, receive him because he has realized that he needs assistance”: a qualitative study exploring preferences for retention on antiretroviral therapy support in Malawi among Lighthouse Clinic clients - O'Bryan, Gillian; Huwa, Jacqueline; Sande, Odala; Thawani, Agness; Berner-Rodoreda, Astrid; Tweya, Hannock; Kiruthu-Kamamia, Christine; Chiwaya, Geldert; Feldacker, Caryl (PLOS ONE, 2025)
Introduction Retention of people living with HIV (PLHIV) on antiretroviral therapy (ART) is critical. Retention is not static: clients cycle in and out of care over the course of treatment. Retention support is also evolving, with interventions like mobile health (mHealth) gaining traction. We aimed to explore ART clients’ perspectives and recommend strategies for improved retention support including a two-way-texting (2wT) mHealth intervention in two clinics in Malawi. Materials and methods We conducted focus group discussions (FGDs) with PLHIV on ART receiving 2wT or standard of care (SoC) retention support to understand client perspectives. FGDs were audio-recorded in Chichewa, translated and transcribed into English. We used the RE-AIM implementation science framework to report findings on the reach, effectiveness, adoption, implementation, and maintenance potential of retention interventions considering individual, clinic/organization, and community factors. Through rapid qualitative analysis, we identified key themes and subthemes. Results Ten FGDs were conducted with 89 ART clients (aged ≥18 years; 55% female): four FGDs among 2wT participants and six among SoC participants. Few differences were observed between 2wT and SoC clients. All clients appreciated accessing at least one form of support and recommended continuous assistance, regardless of age, sex, or duration on ART. Clients wished to be encouraged by other PLHIV to allay common fears. Groups discussed the need for intensified support to retain young clients or those out of care longer. Individual responsibility was identified as necessary, but insufficient, to improve retention: respondents desired a more positive clinic environment to encourage persistence in care. Fear of stigma, unintended status disclosure, and negative interactions with clinic staff prevent some clients from returning to care. Conclusion PLHIV want differentiated, continuous retention support from other PLHIV coupled with a positive clinic environment to promote retention and reengagement in care. As differentiated retention support is expensive, consideration of cost, feasibility, and sustainability is needed.